If two vectors are unit vecors

`hata*hatb=cos(theta)=cos(60^o)=1/2 `

`hata*hata=1` and `hatb*hatb=1`

So `(hata-3hatb)*(mhata+hatb)=mhata*hata-3hatb*mhata+hata*hatb-3hatb*hatb`

Simplifying we get `m(1)-3m(cos(theta))+cos(theta)-3(1)=m-(3m)/2+1/2-3=0`

This gives `-m/2-5/2=0` or `m = -5`

So `m = -5` is our answer.

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.